Efficacy of Brodalumab in Patients with Psoriasis and Risk Factors for Treatment Failure: A Review of Post Hoc Analyses - Mark G. Lebwohl; April W. Armstrong; Andrew F. Alexis; Edward L. Lain; Abby A. Jacobson (Adis, Springer Healthcare, 2024)
Abstract Factors such as obesity, alcohol consumption, and tobacco use are associated with both increased psoriasis severity and inadequate response to systemic and biologic therapies. Obesity is linked to chronic inflammation, which can contribute to psoriasis pathogenesis. Fixed-dose therapies may have reduced efficacy in patients with a higher body mass index, while weight-based dosing can increase the burden of drug-specific side effects. Alcohol and nicotine from tobacco have also been shown to stimulate keratinocyte and immune cell proliferation and production of proinflammatory cytokines. While these risk factors are prevalent among patients with moderate-to-severe psoriasis, their influence on treatment outcomes may be overlooked when evaluating therapeutic options. Brodalumab is a fully human interleukin-17 receptor A antagonist approved for the treatment of moderate-to-severe psoriasis. In this review, we describe the lifestyle-related risk factors associated with decreased response to treatment. We further summarize the post hoc analyses of brodalumab in participant subgroups with moderate-to-severe psoriasis and a history of prior biologic failure, obesity, and alcohol or tobacco use from two phase 3 clinical trials (AMAGINE-2 and AMAGINE-3; ClinicalTrials.gov identifiers: NCT01708603 and NCT01708629, respectively). Our review of clinical trial and real-world data suggests that brodalumab is an efficacious and safe treatment option for patients with lifestyle factors that increase the likelihood of treatment failure, allowing them to achieve skin clearance and improve quality of life.